An Oxygenated and Transportable Machine Perfusion System Fully Rescues Liver Grafts Exposed to Lethal Ischemic Damage in a Pig Model of DCD Liver Transplantation. Issue 7 (July 2017) - Compagnon, Philippe; Levesque, Eric; Hentati, Hassen; Disabato, Mara; Calderaro, Julien; Feray, Cyrille; Corlu, Anne; Cohen, José Laurent; Ben Mosbah, Ismail; Azoulay, Daniel
Abstract : Background: Control of warm ischemia (WI) lesions that occur with donation after circulatory death (DCD) would significantly increase the donor pool for liver transplantation. We aimed to determine whether a novel, oxygenated and hypothermic machine perfusion device (HMP Airdrive system) improves the quality of livers derived from DCDs using a large animal model. Methods: Cardiac arrest was induced in female large white pigs by intravenous injection of potassium chloride. After 60 minutes of WI, livers were flushed in situ with histidine-tryptophan-ketoglutarate and subsequently preserved either by simple cold storage (WI-SCS group) or HMP (WI-HMP group) using Belzer-MPS solution. Liver grafts procured from heart-beating donors and preserved by SCS served as controls. After 4 hours of preservation, all livers were transplanted. Results: All recipients in WI-SCS group died within 6 hours after transplantation. In contrast, the HMP device fully protected the liver against lethal ischemia/reperfusion injury, allowing 100% survival rate. A postreperfusion syndrome was observed in all animals of the WI-SCS group but none of the control or WI-HMP groups. After reperfusion, HMP-preserved livers functioned better and showed less hepatocellular and endothelial cell injury, in agreement with better-preserved liver histology relative to WI-SCS group. In addition to improved energy metabolism, this protective effect was associated with an attenuation of inflammatory response, oxidative load, endoplasmic reticulum stress, mitochondrial damage, and apoptosis. Conclusions: This study demonstrates for the first time the efficacy of the HMP Airdrive system to protect liver grafts from lethal ischemic damage before transplantation in a clinically relevant DCD model. Abstract : The authors demonstrate the efficacy of a new machine perfusion system on a pig ischemic injured DCD liver transplantation model through attenuation of inflammatory response, oxidative load, endoplasmic reticulum stress and mitochondrial damage. Supplemental digital content is available in the text.